GEORGE ELIOT’S WORKS IN ENGLISH LITERATURE AND CRITICAL REALISM (Scientific journal of the Fergana State University, 2024)
In the 19th century, there were a number of great representatives of English literature, which reached its peak with critical realism. Through studying of their work, we will have the opportunity to study not only the real life of the time, but also the complex literary expression of the Victorian era, realistic storytelling, metaphor and symbolism, elements of theater, parody, satire and pantomime.George Eliot, who is considered one of the great representatives of the Victorian era, described the social structure of the 19th century in her works and severely criticized it. Through this article, it is possible to get acquainted with the work of the English writer.